PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA DIVISI ENGINEERING PT. GALIH SEKAR SAKTI TANGERANG - Yovi Febryanto; Jublina Oktora (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of physical work environment and job satisfaction on employee performance at PT Galih Sekar Sakti Tangerang. Both partially and simultaneously. The method used is saturated sampling, namely using a sample of 78 respondents. The data analysis technique used is statistical analysis by testing the vadility test, reliability test, classical assumption test, simple linear test, multiple linear test, coefficient of determination, hypothesis t test and hypothesis F test. The results of research on motivation and work discipline on employee performance at PT Galih Sekar Sakti Tangerang are shown by the multiple linear regression equation Y = 1.388 + 0.614 X1 + 0.165 X2. This is evidenced by the results of simultaneous hypothesis testing obtained F value> F table or (280,242> 3.12), this is also reinforced by ρ value <0.05 or (0.000 <0.05). The results of the determination coefficient test of the Motivation variable (X1) and work discipline (X2) provide an influence of 72.2% on performance at PT Galih Sekar Sakti Tangerang. Thus H03 is rejected and Ha3 is accepted. This means that it is proven that there is a significant influence simultaneously between Motivation (X1) and Discipline (X2) on employee performance (Y).